Fresh Graduate Nurses’ Stress during the Transition in the ER during Pandemic: A Scoping Review - Mohammad Dwi Ardianto; Ahsan Ahsan; Yati Sri Hayati (Universitas Muhammadiyah Yogyakarta, 2022)
The COVID-19 pandemic presents obstacles in transitioning newly graduated nurses to professional nurses in the emergency room. The transition period is challenging and stressful, affecting new nurses’ performance. This study aims to identify the stress fresh graduate nurses experienced during the transition to emergency nurses during the pandemic. A scoping review was used to identify (n=17) articles from six databases (ScienceDirect, PubMed, Proquest, Willey Library, Sega Journal, and EBSCO). An article search used the keywords with the Boolean operator “New Graduate Nurse OR Fresh Graduate Nurse OR Novice Nurse AND Adaptation OR Transition AND Emergency AND Stress” to search the literature for the last five years. The results showed that during the transition period to becoming an emergency nurse during a pandemic, newly graduated nurses experienced mild to severe stress caused by an increased workload, lack of knowledge, and competence. High stress on fresh graduate nurses is also related to the work environment and lack of experience. However, not many studies discuss the influence of organizational factors on stress levels during the transition period. This study’s results suggest providing a support program for new nurses working in the emergency room to reduce the level of stress experienced.